Dienogest in the treatment of endometriosis-associated pelvic pain: a 12-week, randomized, double-blind, placebo-controlled study - Strowitzki, Thomas; Faustmann, Thomas; Gerlinger, Christoph; Seitz, Christian (European journal of obstetrics & gynecology and reproductive biology, 2010)
Objective - To investigate the efficacy and safety of oral dienogest 2mg compared with placebo in the treatment of endometriosis-associated pelvic pain (EAPP). - Study design - This was a 12-week, randomized, double-blind, placebo-controlled, multicenter (n=33) study in Germany, Italy, and Ukraine of 198 women aged 18-45 years with laparoscopically confirmed endometriosis and EAPP score ≥30mm on a visual analog scale (VAS). Dienogest 2mg or placebo was administered orally once daily. The primary efficacy variable was absolute change in EAPP from baseline to Week 12, as determined by the target variables of change in VAS score and change in intake of supportive analgesic medication (ibuprofen) for pelvic pain. - Results - Mean reductions in VAS score between baseline and Week 12 in the full analysis set were 27.4mm and 15.1mm in the dienogest and placebo groups, respectively—a significant score difference of 12.3mm in favor of dienogest (P<0.0001). Changes in intake of supportive analgesic medication were modest in both groups. The primary efficacy measure of absolute change in EAPP demonstrated the superiority of dienogest over placebo. Dienogest was generally well tolerated and few adverse events were associated with therapy. - Conclusions - Dienogest at a dose of 2mg daily for 12 weeks was significantly more effective than placebo for reducing EAPP.